Revisiting shallow glauconite factories: intertwined fates of glauconite and iron - Tribovillard, Nicolas (Comptes Rendus. Géoscience, 2024)
Glauconite is an authigenic green mineral which has been studied extensively because its conditions of formation make it possible to evaluate certain parameters of the sedimentary environments where it is found. The most widespread view is that glauconite forms very slowly from a clay precursor, in environments where low sedimentation rates allow prolonged contact over time between the authigenic mineral and seawater. The latter is seen as the source of some of the chemical elements necessary for the authigenic formation of this phyllosilicate, in particular iron (Fe). Typically, for relatively shallow environments, the distal portion of continental shelves is considered the most suitable formation environment. This review article makes it possible to broaden the spectrum of environments favorable to the growth of glauconite, by identifying environments that experience very shallow deposition depths and relatively high sedimentation rates. These situations are well illustrated by the Jurassic and Cretaceous deposits of the Boulonnais coast (Pas de Calais Strait, between the English Channel and the North Sea). In particular, certain sedimentary deposits show that glauconite could have grown during very early diagenesis. It therefore appears that glauconite can form in relatively varied environments, provided that two main conditions are met: the presence of an abundance of reactive iron and weakly reducing redox conditions. The emphasis of this paper is set on contrasted situations where various sources of iron are involved in the presence of glauconite. Last, abundant-pyrite accumulations imply large supplies of iron for their formation and, as the same time, represent a considerable iron sink with regard to the marine environment.